2020
DOI: 10.1038/s41586-020-2826-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient epoxidation over dinuclear sites in titanium silicalite-1

Abstract: Titanium Silicalite-1 (TS-1) shows an outstanding ability to catalytically epoxidize olefins with hydrogen peroxide (H2O2), leaving only water as byproduct. 1,2 Despite the industrial use of the TS-1/H2O2 system for the production of more than one million tons of propylene oxide per year, 3 the active site structure remains elusive, although it has been studied for almost 40 years by spectroscopic and computational methods. 4-10 TS-1 is a zeotype of MFI structure in which a small fraction of Si-atoms (1-2 %) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
183
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(187 citation statements)
references
References 47 publications
2
183
0
2
Order By: Relevance
“…in 1986, [3] resulted in the emergence of heterogeneous catalysts of practical use for the liquid‐phase oxidation of organic compounds at laboratory and industrial scale, particularly propene to propene oxide using H 2 O 2 as the terminal oxidant [4–7] . The catalytic performances of crystalline microporous titanium‐silicalites TS‐1 are particularly associated to the structural peculiarities of the silica lattice, among which hydrophobicity nature and pore size of the internal channel system are the most relevant, [8] along with the formation of the reactive hydroperoxo moiety, either on isolated titanium sites [9,10] or on dinuclear sites [11] . Indeed, strong physisorption of small apolar substrates is favored whereas water remains outside the pores (in the liquid phase) thus limiting hydrolysis of the isolated active titanium center.…”
Section: Introductionmentioning
confidence: 99%
“…in 1986, [3] resulted in the emergence of heterogeneous catalysts of practical use for the liquid‐phase oxidation of organic compounds at laboratory and industrial scale, particularly propene to propene oxide using H 2 O 2 as the terminal oxidant [4–7] . The catalytic performances of crystalline microporous titanium‐silicalites TS‐1 are particularly associated to the structural peculiarities of the silica lattice, among which hydrophobicity nature and pore size of the internal channel system are the most relevant, [8] along with the formation of the reactive hydroperoxo moiety, either on isolated titanium sites [9,10] or on dinuclear sites [11] . Indeed, strong physisorption of small apolar substrates is favored whereas water remains outside the pores (in the liquid phase) thus limiting hydrolysis of the isolated active titanium center.…”
Section: Introductionmentioning
confidence: 99%
“…By blocking dopamine (mainly D2) receptors in the brain, haloperidol eliminates dopamine neurotransmission which leads to improvement of psychotic symptoms 35 . Haloperidol can also bind to the sigma-1 and sigma-2 receptors, which are implicated in lipid remodeling and cell stress response 12 . As reported by Gordon et al 12 , the SARS-CoV-2 proteins Nsp6 and ORF9c interact with the sigma-1 receptor and the sigma-2 receptor, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Haloperidol can also bind to the sigma-1 and sigma-2 receptors, which are implicated in lipid remodeling and cell stress response 12 . As reported by Gordon et al 12 , the SARS-CoV-2 proteins Nsp6 and ORF9c interact with the sigma-1 receptor and the sigma-2 receptor, respectively. Moreover, they found that haloperidol decreased viral replication in SARS-CoV-2-infected Vero E6 cells with, based on their reported pIC50 and pCC50 values, a calculated Selectivity Index (SI) of 53.7 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a propylene epoxidation process using hydrogen peroxide (H 2 O 2 ) as an oxidising agent (hydrogen peroxide-propylene oxide, HPPO) has received substantial attention because water is the only coproduct and it shows high PO selectivity (> 95%) 11 . The HPPO process itself is environmentally benign; however, current H 2 O 2 production through the anthraquinone process involves multi-step reactions and produces large volumes of organic waste 12 .…”
Section: Introductionmentioning
confidence: 99%